PDK1 Determines Collagen-Dependent Platelet Ca2+ Signaling and Is Critical to Development of Ischemic Stroke In Vivo. Issue 8 (August 2016) - Münzer, Patrick; Walker-Allgaier, Britta; Geue, Sascha; Geuss, Eva; Hron, Gregor; Rath, Dominik; Eißler, Daniela; Winter, Stefan; Schaeffeler, Elke; Meinert, Monika; Schaller, Martin; Greinacher, Andreas; et al.
Abstract : Objective—: Activation of platelets by subendothelial collagen results in an increase of cytosolic Ca 2+ concentration ([Ca 2+ ]i ) and is followed by platelet activation and thrombus formation that may lead to vascular occlusion. The present study determined the role of phosphoinositide-dependent protein kinase 1 (PDK1) in collagen-dependent platelet Ca 2+ signaling and ischemic stroke in vivo. Approach and Results—: Platelet activation with collagen receptor glycoprotein VI agonists collagen-related peptide or convulxin resulted in a significant increase in PDK1 activity independent of second-wave signaling. PDK1 deficiency was associated with reduced platelet phospholipase Cγ2–dependent inositol-1, 4, 5-trisphosphate production and intracellular [Ca 2+ ]i in response to stimulation with collagen-related peptide or convulxin. The defective increase of [Ca 2+ ]i resulted in a substantial defect in activation-dependent platelet secretion and aggregation on collagen-related peptide stimulation. Furthermore, Rac1 activation and spreading, adhesion to collagen, and thrombus formation under high arterial shear rates were significantly diminished in PDK1-deficient platelets. Mice with PDK1-deficient platelets were protected against arterial thrombotic occlusion after FeCl3 -induced mesenteric arterioles injury and ischemic stroke in vivo. These mice had significantly reduced brain infarct volumes, with a significantly increased survival of 7 days after transient middle cerebral artery occlusion without increase of intracerebral hemorrhage. Tail bleeding time was prolonged in pdk1 −/− mice, reflecting an important role of PDK1 in primary hemostasis. Conclusions—: PDK1 is required for Ca 2+ -dependent platelet activation on stimulation of collagen receptor glycoprotein VI, arterial thrombotic occlusion, and ischemic stroke in vivo. Abstract : Supplemental Digital Content is available in the text.